Assessment of Bangus Culture Livelihood Project in Libmanan, Camarines Sur, Philippines - Agonos, Emily M. (Future Science / FSH-PH Publications, 2024)
The study assessed the bangus culture as the key livelihood initiative of the FishCORAL project of BFAR-V covering the coastal barangays in Libmanan, Camarines Sur. The assessment focused on identifying the enterprise's inputs, outputs, and outcomes and its economic and social impacts on the project beneficiaries. Interviews, focus group discussions, desk reviews, and field surveys were employed to evaluate the project achievements, including using an adopted model for monitoring and evaluation. Descriptive analysis and mixed methods were applied to data analysis. Five associations take turns running the livelihood enterprise through the circular sea cage located at Barangay Bahao. The beneficiaries encountered challenges, such as the high cost of fuel used in going to and from the project site, especially those coming from far barangays; commercial markets were not yet considered for the product due to insufficient volume of harvest; and the association's need guidance in leadership and business management. Typhoons affected the project during its initial operation. Still, since the household size of the beneficiary families is primarily tiny, it is easier for them to sustain the family's basic needs with incomes from fishing and other alternative sources. The fishing households share the livelihood assets available in the community. The project achievements met the criteria for relevance, coherence, availability, and perceived utility viz-a-viz the business objectives. Recommended measures, organizational capability, support systems, and internal disagreements must be addressed to sustain the Bangus culture livelihood project.